Competitive activity indicators in handball. Statistics, analysis, forecast - Popovich, A.; Bezukladnova, L.; Bezukladnov, A.; Goncharova, E. (BIO Web of Conferences, 2020)
The article deals with competition in modern sports. It reached its maximum. The competition is conducted within the limits of thousandths of a second, hundredths of a point, one point and a ball. Therefore, success comes to those teams that carefully prepare for matches. They should prepare physically, functionally and analytically, analyzing the opponent`s game. The research of specialists ` work and review of materials published in domestic and foreign publications are carried out. The most significant analysis indicators of the competitive activity in handball are highlighted. The analysis of games in modern sports is insufficient and requires additional research on this problem.